2023
DOI: 10.3390/app132011342
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of Dig Sequence Effects during Large-Scale Excavation

Danli Li,
Ying Chen,
Bing Dai
et al.

Abstract: The appropriate excavation sequence can improve the overall stability of a foundation pit. In this study, eight schemes were created using FLAC3D to examine the impact of the excavation sequence on a foundation pit by analyzing a deep foundation pit in Nanjing, which had an irregular large rectangle shape. The results show that different excavation sequence schemes and different phases of the foundation pit can change the displacement values and the horizontal displacement type. The min–max normalization metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…According to the investigation report and ref. [24], when the soil is the same, the physical and mechanical properties of the soil layers within the excavation range of the pit are shown in Table 1. In Table 1, Es is the compression modulus, c is the cohesion, φ is the internal friction angle, ν is the Poisson's ratio, and h is the thickness of soil layer.…”
Section: Overview Of the Project And Layout Of Measurement Pointsmentioning
confidence: 99%
“…According to the investigation report and ref. [24], when the soil is the same, the physical and mechanical properties of the soil layers within the excavation range of the pit are shown in Table 1. In Table 1, Es is the compression modulus, c is the cohesion, φ is the internal friction angle, ν is the Poisson's ratio, and h is the thickness of soil layer.…”
Section: Overview Of the Project And Layout Of Measurement Pointsmentioning
confidence: 99%
“…However, the majority of empirical index standards only take into account one influencing element, which has poor precision and dependability. As a result, an increasing number of academics are starting to think about using multifactorial techniques based on mathematical algorithmic models to forecast rockbursts [19,20]. Xue et al [10] optimized the ELM by particle swarm algorithm (PSO), selecting six quantitative rockburst parameters, such as the maximum tangential stress of the surrounding rock, uniaxial compressive strength of the rock, the tensile strength of the rock, the stress ratio, the brittleness ratio of the rock and the elastic energy index, on 344 sets of rockburst cases were learned and validated on the riverside hydropower station, and the results showed that the model has a better prediction effect.Yin et al [21] collected 400 groups of cases through microseismic monitoring data, optimized the CNN-Adam-BO integration algorithm by using adaptive matrix estimation and Bayesian to CNN-Adam-BO integration algorithms, respectively, and compared the model with the continuous wavelet transform and the cross-wavelet transform, which verified the superiority of the model.…”
Section: Introductionmentioning
confidence: 99%
“…The construction of subway stations usually involves the excavation of a foundation pit. As subway stations are usually located in downtown areas, the construction environment may be complicated when considering the surrounding existing buildings, pipelines, main traffic roads, and subways, if any, as well as urban planning in the future [5][6][7]. Therefore, during the excavation of a foundation pit, lateral displacement of the surrounding rocks and settlement of the surrounding ground should be strictly controlled to ensure the safety of the surrounding buildings, structures, and so on.…”
Section: Introductionmentioning
confidence: 99%